Impact of Workplace Spirituality on Organization Citizenship Behavior - Suri, Gunmala (Gyan Management Journal, 2017)
Little has been discussed about workplace spirituality in the organizational sciences. The western researchers and organizations have shown considerable interest in understanding the basics of spirituality and its benefits for workplace. However, still this concept continues to be subjective and not much has been explored in the Indian context. This study while adding to the literature of research on Indian organizations also tries to throw some light on the link between spirituality and business. The research is conducted on 100 employees of ITC ltd. to find the impact of workplace spirituality on Organization Citizenship Behavior. The data was analyzed using SPSS and it was found that there exists a positive relationship between workplace spirituality and four dimensions of OCB -Altruism, Conscientiousness, Courtesy, and Civic virtue and negative relationship with Sportsmanship on ITC employees. It is concluded that spirituality if developed amongst employees in workplaces can make them contribute more to the organizations.